Tool for the modeling and code generation of Software Architectures based on Microservices and Domain Driven Design (DDD) - Trebejo Loayza, Waldo Jefferson (2022)
Different companies that provide digital services must have sophisticated software that allows various operations to be carried out in a timely and safe manner, keeping the program in constant improvement, updating and options to incorporate new market technologies. Many companies still use legacy systems as their main tool for business processes, while others use outdated technologies that limit their ability to upgrade or migrate to modern technologies, turning this scenario into a threat to the security of IT systems with which they operate, which jeopardizes the performance and productivity of the company. This article implements a software architecture modeling and code generation tool based on Microservices and Domain Driven Design (DDD), to facilitate and accelerate the development of software projects and the migration of legacy systems to new independent services, by while using modern technologies to account for interoperability, security, scalability, modularity among other quality attributes. To validate the contribution of the tool, it was validated with experts in software design and construction, which revealed the efficiency and effectiveness of the model and code generation, as well as the acceptance of the tool's usability.